(3UQI GdaJGhis - (3GdSGbRj, UGOb Hf eMeO Hf Ydj , J (B1099 (3g`s ((3MSf Hf CMeO CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdabgGA NjGQ GdYHGO aHYO bGd GdabjQ Edi QHg GdbOjQ UGOb eMeO Hf Ydj GdSGbRj hLeYJ eSGFdg GdeaJi Hg GdhGbYI aj GdeMGce ZGdHG CQOJ Cf CQJHgG Ydi efhG GdcJH JSgjdG ddMcGe JfajYG ddCfGe hSejJgG UQI GdaJGhi(B--s
(3BNQgG (B:s
(3hdh bGd Ef GdEjeGf eNdhb agh cGaQ aj cKjQ ef GdaJGhi hYf GdEeGe Cf GdbQBf ZjQ eNdhb hdh CfcQ BjI aj GdbQBf Ch SNQ HBjI efg caQ Gdcd aj LGeY GdaJGhi aj cJGH CdaGX GdcaQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 186s
(3eYLe GdeDdajf (B1 / 826s
(3cTa GdXfhf (B2 / 1078s
(3gOjI GdYGQajf (B2 / 284s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs